(untitled) (Web of Teachers: Inderscience Research, 2025)
Within the framework of the general scientific and technical progress, the constant introduction of new technologies makes them an integral part of one or another field of medicine. The current trend in the development of surgery is to reduce the invasiveness and trauma of surgical interventions. In connection with the development of surgical technologies, one of the main tasks in surgery is the minimization of surgical trauma and the subsequent reduction of the number of postoperative complications and mortality. as well as the terms of inpatient treatment of patients while maintaining the quality of surgical care. It is possible to achieve this goal in abdominal surgery with the widespread and widespread introduction of endosurgical technologies into everyday practice.